2004
DOI: 10.1021/cm049877d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surface Functionalization and Organo-Tailoring of Synthetic Layer Silicates on the Immobilization of Cytochrome c

Abstract: The utility of various synthetic hectorites for the preparation of active enzyme complexes by simple adsorption processes was examined. The smectites compared include commercially available Laponite RD, mesostructured hectorites (both with and without organic template), and silane-modified mesostructured hectorite. The complexes were evaluated by the amount of cytochrome c that was incorporated and the fraction of enzyme available for redox reaction. The quantity of adsorbed cyt c was determined by optical abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Dramatic responses observed in biomolecules and biomolecular processes involved in interfacial phenomena that involve inorganic surfaces are well demonstrated in biomineralization processes (Zaremba et al, 1996), biomolecular chromatographic separations (Kimura et al, 2004), supported enzyme activities and lifetime (Carrado et al, 2004; Han et al, 2002) and protein folding and denaturation (Charache et al, 1962). Mentioned earlier in Section 2.2, the development of potent wound-dressing materials (blood clotting agents) that are capable of arresting hemorrhage due to traumatic injury is another emerging application using materials chemistry to control bioprocesses (Ellis-Behnke et al, 2006; Fischer et al, 2005; Marris, 2007; Ostomel et al, 2006a) and one of the most effective wound-dressing materials currently available is a nanoporous zeolite called QuikClot® (QC) (Z-Medica).…”
Section: Engineered Nanomaterials: Overview and Recent Advancesmentioning
confidence: 99%
“…Dramatic responses observed in biomolecules and biomolecular processes involved in interfacial phenomena that involve inorganic surfaces are well demonstrated in biomineralization processes (Zaremba et al, 1996), biomolecular chromatographic separations (Kimura et al, 2004), supported enzyme activities and lifetime (Carrado et al, 2004; Han et al, 2002) and protein folding and denaturation (Charache et al, 1962). Mentioned earlier in Section 2.2, the development of potent wound-dressing materials (blood clotting agents) that are capable of arresting hemorrhage due to traumatic injury is another emerging application using materials chemistry to control bioprocesses (Ellis-Behnke et al, 2006; Fischer et al, 2005; Marris, 2007; Ostomel et al, 2006a) and one of the most effective wound-dressing materials currently available is a nanoporous zeolite called QuikClot® (QC) (Z-Medica).…”
Section: Engineered Nanomaterials: Overview and Recent Advancesmentioning
confidence: 99%
“…Phyllosilicates are used in the development of nano-materials, nano-wires and patterned surfaces for nano-biological interfaces [Monnier et al, 1993;Carrado et al, 2004;Suh et al, 2009]. They are also employed, in a form of cation-exchanged sheet silicates, as catalysts in chemical reactions [Ballantine et al, 1984], e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[1,9] Thereby, it is of great importance to shorten the electron-tunneling dis-tance between the redox center of the protein/microbe and the electrode to enable direct electron transfer. [9] Recent studies have demonstrated that direct electrochemistry can be realized by uniquely nanostructured electrodes, [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] which could access the embedded redox centers of proteins or microbes while increasing surface area, enhancing mass transport and controlling the electrode microenvironment. [1,[10][11][12][13][14] Further, some physico-chemical properties, including conductivity, hydrophilicity and interfacial resistance are essential to enhance the direct electron transfer rate.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Highly porous metal oxide nanostructures (TiO 2 , ZnO, etc.) [8,[18][19][20] and some layered inorganic materials (clay, phosphates, titanate) [21][22][23][24] are superior to many carbon and metal nanostructures in hydrophilicity and sometimes in specific surface area. However, a lack of good electrical conductivity limits their performance in direct electrochemistry.…”
Section: Introductionmentioning
confidence: 99%